Technological disaster factors - Shaluf, Ibrahim M.; Ahmadun, Fakhru'l-Razi; Shariff, Abdul Rashid (Elsevier, 2003)
Major Hazard Installations (MHIs) deal with the hazardous substances which exceed the threshold quantity. Although MHIs are safe organizations, they cannot fail due to a single error. However, due to their high complexity, the designer and the operator make errors during the design, and operation of the plants. Consequently, the technical, operational and organizational errors may lead to a major accident. The world has seen many incidents due to the operation of the MHIs. Malaysia has experienced several technological disasters. Four investigation reports have been reviewed in detail. This paper reviews the causes of the technological disasters in general. This paper also summarizes the causes of the technological disasters in Malaysia. Finally the paper rearranges the technological disaster causes and errors.